BENEFIT AND CHALLENGES OF PROJECT-BASED LEARNING - ELIAS, SOFIA; ABDUL KARIM, NOORHUDA (Human Sustainability Procedia, 2018)
Project based learning has become a popular practice in Malaysian educationfrom pre-school until the higher learning institutions. However, there are still much to be researched about this learning technique in Malaysian education scenario; especially at higher learning institutions. At the higher learning institutions, this learning technique is commonly adapted for co-curriculum subjects. Co-curriculum subjects may differ from one institution to another; and as such, so are the practice and management of such subjects. Naturally in such diverse environment that deals with relatively matured students, issues pertaining to what constitutes as quality and successful project-based learningare of great importance. This paper aims to discuss the benefits as well as challenges in implementing project-based learning in private higher learning education; in specific from the experience of UNITAR International Universityin conducting co-curriculum courses for more than 7 years